Parents support to the social development of school-age children who use smartphone - Indriatie Indriatie; Aida Novitasari; Yohanes K. Windi (International Journal of Public Health Science (IJPHS), 2022)
Smartphone is widely used among school-age children. Excessive use of smartphone leads to health and psychological problems for children. Parents are responsible for ensuring that their children use smartphone properly. This study aimed to identify the support of parents to the social development of school-aged children using smartphone. It is a correlational analytic study involved 200 respondents who recruited through clusters random sampling procedure. The variables are social development and parents support for children who using smartphone. The study employed Spearman correlation rank was used to test the association between variables for data analysis. The results obtained that the children who use smartphone do not experience social development disruption. Their parents provide sufficient support when they are using smartphone. The statistical analysis shows the significant correlation between the social development of school-aged children who use smartphone and their parents support. Parents are responsible for providing sufficient support to avoid social development disruption of their children due to smartphone use. The study suggests that parents should maintain their support and actively monitor smartphone use, including the content, duration, and frequency of using smartphone.